An ergometer based study of the role of the upper limbs in the female rowing stroke - Jones, J. A.; Allanson-Bailey, L.; Jones, M. D.; Holt, C. A. (Procedia Engineering, 2010)
Optimisation of the rowing technique is of paramount importance in improving performance and minimising injury risks. This report aims to investigate and compare arm kinematics between two commonly used commercial gymnasium rowing ergometers; five female amateur rowers were tested on the Concept2(TM)and the RowPerfect(TM). Qualisys(TM)(Sweden) motion analysis system was used to measure stroke kinematics. Results indicate that subjects on the Concept2(TM)tended to "jerk" (impulse load) the handle during the rowing stroke in an attempt to achieve greater power. Arm kinematics indicate that the RowPerfect(TM)appears to be more effective for recreational users compared to the Concept2(TM).